TEKNIK PEMELIHARAAN INDUK IKAN BAWAL BINTANG (TRACHINOTUS BLOCHI) DI BALAI BENIH IKAN LAUT (BBIL), PULAU TIDUNG KEPULAUAN SERIBU - RIZA TRIANZAH; CATUR PRAMONO ADI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2023)
Fish rearing in aquaculture activities aims to produce consumption-sized fish. In rearing activities, fish are encouraged to grow optimally until they reach marketable size by providing an optimal fish living media environment, and providing the right amount, quality, method, time and control of pests and diseases. So it is necessary to plan in advance in the rearing process so that the implementation is easier and more precise so that it can produce good goldfish for consumption. Carp rearing production planning is an activity to regulate the process of raising star pomfret fish which consists of land preparation, seed sowing, feeding, water quality parameters, pests and diseases, and harvesting. The objectives of the research are: 1). Find out potential parent pomfret fish whose gonads have matured. 2). Knowing the quality of water for rearing prospective broodstock. From the results of research activities that have been carried out at BBIL, the following conclusions were obtained: 1). Prospective parent pomfret fish whose gonads have matured can be identified by genotype and phenotype. Where the female weighs more than 2 kg and is > 35 cm long, the body shape is rounder and larger than the male, the egg pellets are visible, the eggs are yellowish in color, the eggs release a sticky fluid when held. Meanwhile, the male parent weighs over 1.5 kg and is >35 cm long, his body looks slender and elongated and smaller than the female, the sperm is milky white and the sperm feels sticky when held. 2). The quality of the water when rearing prospective broodstock for pomfret fish has been determined by measuring temperature, salinity and pH directly in situ. Where temperatures in weeks 1, 2, and 3 ranged from 30.6oC, 31.2oC, and 29.7oC; Salinity in weeks 1, 2, and 3 ranged from 32 ppt, 32.14 ppt, and 31.42 ppt; pH at weeks 1, 2, and 3 ranged from 7.61, 7.74, and 7.79. ABSTRAKPembesaran ikan dalam kegiatan budidaya perairan bertujuan untuk menghasilkan ikan ukuran konsumsi. Dalam kegiatan pembesaran, ikan didorong untuk tumbuh secara maksimum hingga mencapai ukuran pasar (marketable size) melalui penyediaan lingkungan media hidup ikan yang optimal, dan pemberian pakan yang tepat jumlah, mutu, cara, waktu serta pengendalian hama dan penyakit. Sehingga perlu perencanaan terlebih dahulu dalam proses pembesaran agar pelakasanaannya lebih mudah dan tepat supaya bisa menghasilkan ikan mas konsumsi yang baik. Perencanaan produksi pembesaran ikan mas merupakan kegiatan untuk mengatur proses dalam pemeliharaan ikan bawal bintang yang terdiri dari persiapan lahan, penebaran benih, pemberian pakan, parameter kualitas air, hama dan penyakit, dan pemanenan.Tujuan dari penelitian adalah: 1). Mengetahui calon induk ikan bawal bintang yang sudah matang gonad. 2). Mengetahui kualitas air pemeliharaan calon induk. Dari hasil kegiatan penelitian yang sudah dilaksanakan di BBIL diperoleh kesimpulan sebagai berikut: 1). Calon induk ikan bawal bintang yang sudah matang gonad dapat diketahui secara genotif dan fenotif. Dimana pada betina memiliki bobot diatas 2 kg dan panjang > 35 cm, bentuk tubuh lebih bulat dan besar dibanding jantan, butiran telurnya telah terlihat, telur telah berwarna kekuningan, telur telah melepaskan cairan pelekat apabila dipegang. Sedangkan pada induk jantan memiliki bobot diatas 1,5 kg dan panjang >35 cm, tubuhnya terlihat ramping dan memanjang serta lebih kecil dibanding betina, sperma berwarna putih susu dan sperma terasa lengket apabila dipegang. 2). Kualitas air pada pemeliharaan calon induk ikan bawal bintang telah diketahui dengan melakukan pengukuran suhu, salinitas dan pH langsung secara insitu. Dimna suhu pada minggu ke-1,2, dan 3 berkisar 30,6oC, 31,2oC, dan 29,7oC; Salinitas minggu ke- 1,2, dan 3 berkisar 32 ppt, 32,14 ppt, dan 31,42 ppt; ph pada minggu ke-1,2, dan 3 berkisar 7,61, 7,74, dan 7,79.